Solution NMR structures provide first structural coverage of the large protein domain family PF08369 and complementary structural coverage of dark operative protochlorophyllide oxidoreductase complexes - Pulavarti, Surya VSRK (2013)
High-quality NMR structures of the C-terminal domain comprising residues 484-537 of the 537-residue protein Bacterial chlorophyll subunit B (BchB) from Chlorobium tepidum and residues 9-61 of 61-residue Asr4154 from Nostoc sp. (strain PCC 7120) exhibit a mixed α/β fold comprised of three α-helices and a small β-sheet packed against second α-helix. These two proteins share 29 % sequence similarity and their structures are globally quite similar. The structures of BchB(484-537) and Asr4154(9-61) are the first representative structures for the large protein family (Pfam) PF08369, a family of unknown function currently containing 610 members in bacteria and eukaryotes. Furthermore, BchB(484-537) complements the structural coverage of the dark-operating protochlorophyllide oxidoreductase (DPOR).